MODERN TRENDS IN BUSINESS IN THE FUNCTION OF BUSINESS SUCCESS - Gordana Nikcevic\' (Agora International Journal of Economical Sciences (AIJES), 2023)
The aim of this paper is to point out the importance of new trends in the business of modern organizations. Emphasis is placed on the processes that characterize modern organizations, namely: globalization, sustainability, information technology and modern organizational structures. The paper analyzes the extent to which modern organizations fit into the trends of globalization and sustainability, and the extent to which they apply modern information technologies and organizational structures. In order to have a more successful analysis, the advantages and disadvantages of these trends have been identified. The paper shows that the successful operation of modern organizations depends on the degree to which they have managed to master these trends and implement them in their business strategies. All these processes result in connecting and networking organizations, developing democratic relations in management and decision -making, which has a positive impact to greater employee motivation and more efficient business.
Keywords: 330